PENERAPAN PENDEKATAN BERMAIN BOLA EKOR UNTUK MENINGKATKAN HASIL BELAJAR LEMPAR TURBO PADA SISWA KELAS V SDN KUTOWINANGUN 11 KECAMATAN TINGKIR KOTA SALATIGA TAHUN PELAJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to determine the effectiveness of the game ball tailed toward improving student learning outcomes SDN classes Kutowinangun Tingkir Salatiga District 11 Academic Year 2012/2013. The method used in this research is a classroom action research techniques of data analysis using descriptive percent, while the data retrieval technique using the method of observation and documentation. Based on the research that in the first cycle, the percentage achievement of affective aspects by 73%, 72% cognitive and psychomotor aspects of 67%. So that the overall absorption of the material in the first cycle reaches 73% with an average of 73. So stated that in the first cycle of learning has not been successful. While in the second cycle completeness percentage of students on the affective aspects of reaching 92%, reaching 72% cognitive and psychomotor aspects percentage reaches 71% with complete learn cycle II was 86% with an average of 75. So it can be said that there is an increase in learning outcomes from the first cycle to the second cycle of 24%, ie from 64% to 86% of students were able to reach the limit completely. Thus the study has been successful. Conclusion of this research is the application of the approach play ball tails effective in improving learning outcomes throwing a turbo on fifth grade students of SDN 11 Kutowinangun Tingkir Salatiga District Academic Year 2012/2013.